2020
DOI: 10.47994/usbad.775002
|View full text |Cite
|
Sign up to set email alerts
|

Türki̇ye’de Di̇nleme Eği̇ti̇mi̇ni̇n Geldi̇ği̇ Nokta (2017-2019 Yillari)

Abstract: İntihal: Bu makale intihal.net yazılımınca taranmıştır. İntihal tespit edilmemiştir. Plagiarism: This article has been scanned by intihal.net. No plagiarism detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…It was observed in our study that the studies on listening were mostly carried out with secondary school students (f=68), followed by non-native speakers (f=53), and primary school students (f=33). The literature indicates that secondary school students are the preferred target audience in most of the postgraduate studies on listening (Doğan and Özçakmak, 2014;Kemiksiz, 2017;Kardaş, Çetinkaya, and Kaya, 2018;Doğan Kahtalı, Oğuz, Cayhan, and Taşkın, 2020;Kavum, 2021;Göçer and Bıyık, 2022;Potur, 2023). Generally, findings in the literature suggest that studies on listening focusing on preschool, primary school, and high school levels are not at the desired level (Doğan and Özçakmak, 2014;Kardaş, Çetinkaya, and Kaya, 2018;Doğan Kahtalı, Oğuz, Cayhan, and Taşkın, 2020;Göçer and Bıyık, 2022).…”
Section: Target Audiencesmentioning
confidence: 99%
See 3 more Smart Citations
“…It was observed in our study that the studies on listening were mostly carried out with secondary school students (f=68), followed by non-native speakers (f=53), and primary school students (f=33). The literature indicates that secondary school students are the preferred target audience in most of the postgraduate studies on listening (Doğan and Özçakmak, 2014;Kemiksiz, 2017;Kardaş, Çetinkaya, and Kaya, 2018;Doğan Kahtalı, Oğuz, Cayhan, and Taşkın, 2020;Kavum, 2021;Göçer and Bıyık, 2022;Potur, 2023). Generally, findings in the literature suggest that studies on listening focusing on preschool, primary school, and high school levels are not at the desired level (Doğan and Özçakmak, 2014;Kardaş, Çetinkaya, and Kaya, 2018;Doğan Kahtalı, Oğuz, Cayhan, and Taşkın, 2020;Göçer and Bıyık, 2022).…”
Section: Target Audiencesmentioning
confidence: 99%
“…The literature indicates that secondary school students are the preferred target audience in most of the postgraduate studies on listening (Doğan and Özçakmak, 2014;Kemiksiz, 2017;Kardaş, Çetinkaya, and Kaya, 2018;Doğan Kahtalı, Oğuz, Cayhan, and Taşkın, 2020;Kavum, 2021;Göçer and Bıyık, 2022;Potur, 2023). Generally, findings in the literature suggest that studies on listening focusing on preschool, primary school, and high school levels are not at the desired level (Doğan and Özçakmak, 2014;Kardaş, Çetinkaya, and Kaya, 2018;Doğan Kahtalı, Oğuz, Cayhan, and Taşkın, 2020;Göçer and Bıyık, 2022). In our study, although not sufficient, it was found that compared to the period of 2014-2018, there was a proportional increase in the number of postgraduate studies targeting preschool and primary schools from 2019 to 2023.…”
Section: Target Audiencesmentioning
confidence: 99%
See 2 more Smart Citations